Simultaneous determination of benzene, toluene and xylene (BTX) by Au nanoparticles (AuNP) anchored in reduced graphene oxide electrode - Carlos Braga Alves, Ismael; Ribamar Nascimento dos Santos, José; Pereira Marques, Edmar; Carvalho Martiniano de Azevedo, Lorena; Azevedo Beluomini, Maísa [UNESP]; Ramos Stradiotto, Nelson [UNESP]; Lopes Brandes Marques, Aldaléa (Wiley, 2024)
This work reports the development of an electrochemical sensor for the simultaneous determination of benzene, toluene and xylene (BTX). The sensor was prepared by coating the glassy carbon electrode (GCE) with reduced graphene oxide (RGO) film, decorated with gold nanoparticles (AuNP), by electrodeposition. Surface modification with AuNP/RGO-GCE favored the electron transfer process and increased the active area, providing greater sensitivity for the sensor. The AuNP/RGO-GCE sensor was characterized by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and scanning electron microscope (SEM). Quantitative analyses of BTX were carried out using the differential pulse voltammetry (DPV) technique, after optimization of the parameters that influence the sensor performance. The sensor showed a linear response in the 30–240 μM concentration range, with a detection limit range of 1.8–2.2 μM, 2.2–2.7 μM, and 2.0–2.6 μM, and quantification limit range of 6.2–7.3 μM, 7.2–8.9 μM, and 6.6–8.8 μM, respectively for B, T and X. In addition to the satisfactory repeatability and stability, in the determination of BTX, the method still showed good selectivity even in the presence of molecules with similar chemical structure, such as: catechol, p-benzoquinone, resorcinol, ethanol, pyrene and in the presence of K+, Mg2+ and Pb2+ ions. The device was successfully applied for the determination of the analytes (BTX) in water samples from fuel station separator boxes, where recovery rates close to 100 % (97.8 % to 103.1 %) were obtained. The results obtained suggest that the AuNP/RGO-GCE sensor has strong potential for detecting BTX in wastewater discharge from industrial processes.
Keywords: Au nanoparticles; BTX; electrochemical determination; reduced graphene oxide